Elemente de tehnici de fizioterapie la animale - Eugenia Dumitrescu; Romeo Teodor Cristina (Medicamentul Veterinar)
The various techniques of physiotherapy in animals are increasingly known and used in animals being considered therapeutic adjuvants, highly valued recently in veterinary clinics. This review represents, in a nutshell, the reiteration of several base elements of physiotherapy used more and more frequently in animals (chiropractic, electrotherapy, ultrasound, laser therapy, magnetotherapy, moxibustion, hydrotherapy). We mention that this material appeared at the request of those interested in this field and is an integral part of the work Elements of alternative and complementary therapy in veterinary medicine, authors Eugenia Dumitrescu and Romeo T. Cristina, published in 2015 at Solness Publishing House in Timisoara.